2018
DOI: 10.21475/ajcs.18.12.08.pne1008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the antioxidant and glyoxalase enzyme activities in leaves of two Moroccan sorghum ecotypes with differential tolerance to nitrogen stress

Abstract: Nitrogen stress as well as other stresses can negatively impact the plant development and metabolism. Generally, stress factors increase the reactive oxygen species (ROS) and methylglyoxal (MG) production, which may, in the absence of effective protective mechanisms, induce irreparable metabolic dysfunction and death. The effect of different amounts (from deficiency to excess) of nitrate, ammonium or nitrate combined to ammonium, on enzyme activities of antioxidant and methylglyoxal detoxification systems of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“… 42 , 43 In this study, it was shown that the activities of SOD and APX were significantly higher in 780016B/12 superior (F) than in 92011 (G) under low nitrogen stress ( Figure 8a, d ). This kind of antioxidant defense system helps to protect photosynthetic organs from oxidative stress induced by N deficiency, 44 indicating that these two antioxidant enzymes may be closely related to the LN tolerance capacity of 780016B/12 superior (F). However, the POD activity of 92011 (G) was much higher than that of 780016B/12 superior (F).…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 In this study, it was shown that the activities of SOD and APX were significantly higher in 780016B/12 superior (F) than in 92011 (G) under low nitrogen stress ( Figure 8a, d ). This kind of antioxidant defense system helps to protect photosynthetic organs from oxidative stress induced by N deficiency, 44 indicating that these two antioxidant enzymes may be closely related to the LN tolerance capacity of 780016B/12 superior (F). However, the POD activity of 92011 (G) was much higher than that of 780016B/12 superior (F).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a comparative study conducted in the two sorghum genotypes viz. 3P4 and 4P11, has revealed an increase in GLYI and GLYII activities in the plants subjected to both N-deficient and N-excess conditions, especially in the case, where ammonium was used as a N source [58]. In a similar context, the impact of MG in contributing towards NH 4 + toxicity symptoms in Arabidopsis has been recently studied [59].…”
Section: Discussionmentioning
confidence: 99%
“…When plants are exposed to stress factors, an increase of the reactive oxygen species (ROS) is observed [47]. To maintain ROS under normal levels, plants can evolve a multitude of protective mechanisms, among of the them, the activation of the antioxidative enzymes such as, SOD, GST and GR [48].…”
Section: Effect Of Ure On Plant Growth and Oxidative Stress Metabolism Of Wheat Plantsmentioning
confidence: 99%
“…The GSH is used in several redox reactions, among of them, those responsible for the amino acid transport and protein and DNA synthesis [51]. High ratio of GSH/GSSG was also reported to be required for accelerating the H2O2 scavenging pathway, especially when plants are facing stressful conditions [48,52]. The increase in plant height and fresh weight at the concentration of 25% of seaweed could explain the high level of the GR enzyme at this condition, to allow synthesis of high levels of GSH required for the metabolic pathways implicated in biomass production and also to cope with the eventual stressful conditions that face wheat plants.…”
Section: Effect Of Ure On Plant Growth and Oxidative Stress Metabolism Of Wheat Plantsmentioning
confidence: 99%
See 1 more Smart Citation